HUMANS’ MICROBIOME IMPACT ON DISEASE - Singh, Bhim; Kumar, Rajesh (International Journal of Psychosocial Rehabilitation, 2021)
Hundreds of billions of microbes have coexisted with humans and now live on and within them. Microbial imbalance in the intestine is regulated by a variety of factors, and it has a strong link to human health and disease. The human microbiome is made up of bacteria, archaea, viruses, and eukaryotes that exist both within and outside our bodies. In both health and illness, these organisms have an impact on human physiology, promoting or inhibiting metabolic and immunological processes. Microorganisms’ colonize a wide range of sites on and inside the human body, adapting to the niche’s particular properties. As a result of their biological interaction with the immune system throughout time, the indigenous organisms in the human body have become highly adapted to the immune system. The precise metabolic activities and functions of these microorganisms within each bodily location are accounted for by the inherent diversity of the human microbiota. As a result, it’s critical to comprehend the human microbiome’s microbial composition and behaviors as they relate to health and disease.